THE PRACTICE OF DOWER AND DOWRY IN MUSLIM MARRIAGE IN BANGLADESH: A LEGAL ANALYSIS - Ferdousi, Nahid (Jurnal Syariah, 2019)
Dower and dowry have become two common terms of Muslim marriage in Bangladesh. Dower is an exclusive right of Muslim wife to receive a part of the husband’s income at any time after marriage. Though it enhances the status and security of the Muslim, there is a situation where a wife does not receive dower from husband due to various socio-legal reasons. Moreover, there is a situation where a woman loses her legal rights of dower while she is entitled under both the Shariah and statutory laws. Then, there is an occurrence where a woman and her family become the victims of dowry practice by the husband even though it is un-Islamic. Nevertheless, there are some challenges to recover the dower but a dowry victim does not receive justice from laws and tradition. The article analyses the challenges of woman’s right for dower practice under the Shariah and Statutory laws and the impact of the traditional practice of dowry offer some suggestions for improving the family justice in Bangladesh.